Impact of Unsafe Abortion: A Case Report - Soni, M; Meena, D; Vyas, J; Khajotiya, S (Nepal Journal of Obstetrics and Gynaecology, 2012)
Legalisation of abortion is a necessary but insufficient step towards improving women’s health, if it is not supported by a strong back-up of skilled providers, adequate facilities and easy access. We report a case of a 20-year old female, who presented with uterine, vaginal and rectal perforation with macerated fetus in the abdominal cavity with severe sepsis after an attempted unsafe abortion. NJOG 2011 Nov-Dec; 6 (2): 47-48 DOI: http://dx.doi.org/10.3126/njog.v6i2.6757